(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This Study Aims To Look For The Role Of The Imaginary In Establishing A New Relationship Between The Reader And History, Thanks To The Novel’s Ability To Restore Awareness Of What Has Happened In The Past, The Novels Of The Algerian Writer "Elhabib Sayeh" (Modibon Lawno Damihim Fi Kaffi) And (Colonel Zubarber) Address This Subject By Dealing With Two Important Periods In The Contemporary History Of Algeria. By Investing The Most Important Questions Raised In Both Versions, The First Questioned The Period Of The Ordeal And Raised The Question Of Violence Between History And Religion, Or A Conflict Between The Narrative Of The Revolution And That Of Terrorism, It Also Addressed The Role Of Violence In Changing The Identity Path, The Second Has Given Us A Narrative Revolution From A New Perspective, The Receiver Again Asks Questions About What Happened, And Focused On The Role Of Historical Memory In The Development Of The Notion Of Identity. This Reading Invests What Has Been Achieved By Research In The Field Of The Relationship Of The Novel With History, Because Narration Is The Element That Drives This Relationship And Weaves It. Keywords: Imaginary, History, Narration, Identity, Memory, Violence.